Real World Experience of Long Term Treatment Outcome in Hormone Receptor-positive Metastatic Breast Cancer with or without Everolimus and Exemestane after Prior Aromatase Inhibitor - Dajsakdipon, Thanate; Konmun, Jitprapa; Udomsubpayakul, Umaporn; Dejthevaporn, Thitiya (Asian Pacific Journal of Cancer Care, 2021)
Background: Everolimus/exemestane has been shown to improve progression-free survival in patients with endocrine-resistant metastatic breast cancer. The regimen has been well-accepted despite lack of survival benefit. In real-life setting, patients were not well-selected and hence benefit of such treatment may not be as robust. Method: This is a retrospective review of 143 hormone receptor (HR) positive, HER-2 negative MBC patients who progressed on nonsteroidal aromatase inhibitors. Patients who received everolimus/exemestane in any treatment lines (EE group) were compared to patients who never received everolimus (NE group). Primary end point was survival adjusted to prognostic factors. Results: There were 52 patients in EE group and 91 in NE group with mean age of 58.6 years. Median follow-up time was 51 months. Unadjusted median OS was significantly longer in EE [33 vs 25 months, HR 0.66 (95%CI 0.44-0.998); p = 0.049]. In univariate analysis, factors affecting survival included numbers of metastatic sites, bone metastasis, EE treatment and numbers of treatment lines. Independent factors that remained significant in multivariate analysis were treatment lines [HR 0.71 (95%CI 0.63-0.79); p < 0.05] and numbers of metastatic sites. Median numbers of treatment line after NSAI failure was 5.2 vs 3.6 lines in EE and NE, respectively. Conclusion: In this real-life practice data, pts with HR positive, HER-2 negative MBC who had progressed on NSAI, sequential use of multiple treatment regimens of endocrine and chemotherapy is essential to longer survival. Everolimus/exemestane may have contributed, to a lesser extent, to this improvement in survival.